Early Ordovician Connell Mountain porphyry Cu deposit, Woodstock, New Brunswick, Canada: Geochemical, S isotopic, and Re–Os geochronologic constraints on adakitic slab failure magmatism - Lentz, David R.; Creaser, Robert A.; Thorne, Kathleen G.; Yousefi, Fazilat (Atlantic Geoscience, 2026)
The Early Ordovician subvolcanic Gibson intrusive complex, located near Woodstock, New Brunswick, Canada, is composed of the main Gibson pluton, and mineralized marginal (satellite) stocks at Connell Mountain, Bulls Creek, and the tuffisitic diatreme at Sharp Mountain. The high-level Connell Mountain hornblende-plagioclase porphyritic tonalite stock (~100 MPa) is a small cupola, 1500 m north of the main Gibson pluton, and hosts low-grade porphyry copper mineralization (23 Mt at 0.18% Cu). These intrusions are calc-alkalic, metaluminous, and magnesian, with low TiO2 (0.16 to 0.38 wt.%) and Zr (67 to 92 ppm), and low Nb (4.3–7.7 ppm) and Ta (<0.5 ppm), low Y (5 to <20 ppm) and Yb (1.0 to 2.9 ppm), which are consistent with adakitic slab failure magmatic rocks. Sulphur isotopic compositions of pyrite and chalcopyrite from the porphyry and altered sedimentary rocks range from δ34S = +9.3 to +12.5‰ (n = 8), indicating derivation from carbonaceous sulphidic metasedimentary rocks of the Cambrian–Ordovician Woodstock Group. The crystallization age of the Connell Mountain tonalite (474.5 +1/-4 Ma, U–Pb zircon, previously published) is similar to a previously determined U–Pb zircon age of the Gibson granodiorite, which is coeval with the volcanic-dominated Meductic Group (470–477 Ma) located just to the west. Three Re–Os model ages of 475.6 ± 1.2, 475.8 ± 1.2, and 476.5 ± 1.2 Ma from three textural varieties of molybdenite at Connell Mountain (Re = 333, 642, and 1562 ppm) yield a weighted average model age of 475.9 ± 1.1 Ma indistinguishable from those earlier zircon U–Pb ages, so the porphyry and Cu mineralization at Connell Mountain are related to a hypabyssal phase of the Gibson Granodiorite that is exposed (part of the Gibson Intrusive Complex).